Synthesis and property study of phthalocyanine tetraimides as solution processable electron acceptors. (February 2020) - Zhao, Xiaohong; Huang, Xiaoshuai; Hu, Ming; Chai, Wenqiang; Yuan, Zhongyi; Liu, Xia; Hu, Yu; Cai, Chunsheng; Chen, Yiwang
Abstract: Soluble phthalocyanine tetraimides (PcTIs) with hydrophobic side chains were designed and synthesized via three routes. Their absorption, fluorescence, electrochemistry, stability, charge mobility, and geometries were investigated. These planar conjugation compounds with intense absorption in 550–850 nm, deep lowest unoccupied molecular orbitals of −3.92 to −3.98 eV, decomposition temperature higher than 400 °C, and highest electron mobility of 4.88 × 10 −4  cm 2  V −1  s −1 (SCLC) were excellent solution processable acceptors. Bulk heterojunction solar cells based on acceptor CuPcTI-C11 reached a power conversion efficiency of 1.17% which is the highest value among phthalocyanine derivatives. Graphical abstract: Image 1 Highlights: Soluble phthalocyanine tetraimides (PcTIs) as electron acceptors were designed and synthesized via three routes. Three compounds with strong absorption, good thermal stability, and high electron mobility are potential acceptors. OSCs based on acceptor CuPcTI-C11 reached PCE of 1.17%, the highest value among solution processable Pc derivatives.